Energetics‐Based Estimation of the Diapycnal Mixing Induced by Internal Tides in the Andaman Sea. Issue 4 (22nd April 2021) - Peng, Shiqiu; Liao, Jiawen; Wang, Xiaowei; Liu, Zhiyu; Liu, Yanliang; Zhu, Yuhang; Li, Bingtian; Khokiattiwong, Somkiat; Yu, Weidong
Abstract: The Andaman Sea (AS) is characterized by surprisingly weak stratification in its deep basin in drastic contrast to the nearby Bay of Bengal (BoB), presumably due to strong diapycnal mixing fertilized by the dissipation of internal tides. Here, we report on the first estimates of tidal mixing in the AS using idealized numerical simulations resolving the generation and evolution of low‐mode internal tides. The estimation is based on a diagnostic analysis of the energetics of the simulated internal tides of both local and non‐local origins. The results highlight the dominant role of the internal tides generated in the channels along the western boundary island chain in energizing diapycnal mixing in the entire AS. Tidal dissipation and mixing in the deep basin of the AS are found to be highly elevated, with the depth‐integrated dissipation rate and the diapycnal diffusivity being O (10 −2 –10 ) W m −2 and O (10 −3 –10 −2 ) m 2 s −1, respectively, both of which are 1–2 orders of magnitude larger than those in the deep BoB. These model‐based estimates of tidal mixing are in general consistent with those from in situ conductivity‐temperature‐depth (CTD) measurements using the fine‐scale parameterization. Our results suggest that the oft‐used tidal mixing parameterization considering only local internal tide generation would underestimate the depth‐integrated tidal dissipation in the AS by several orders of magnitude, highlighting therefore the necessity of considering contributions of non‐local internal tides in parameterizing tidal dissipation and mixing in marginal seas like the AS. Plain Language Summary: The Andaman Sea (AS) is a marginal sea of the eastern Indian Ocean featured by strong internal tides, the dissipation of which can induce elevated turbulent mixing that tends to homogenize water properties at different depths. Hydrographic measurements suggest that the deep water in the AS is indeed rather well mixed, in drastic contrast to that in the nearby Bay of Bengal (BoB). Yet, knowledge on mixing characteristics in the AS remains very limited. To this end, we provide the first energetics‐based estimation of internal‐tide‐induced turbulent dissipation and mixing in the AS using idealized numerical simulations resolving the generation and evolution of low‐mode internal tides. Our main finding is that turbulent dissipation and mixing are elevated in the deep AS due to the dissipation of internal tides originated from the channels along the western boundary island chain. These model‐based estimates are supported by the mixing estimates from in situ measurements, and suggest that turbulent mixing in the deep AS is larger than that in the deep BoB by 1–2 orders of magnitude. This provides a physical interpretation for the noted drastic contrast in the distribution of water properties in the AS and BoB. Key Points: The energetics‐based estimation of tidal mixing takes into account the contributions of both locally and remotely generated internal tides The internal tides in the western boundary island chain are the dominant energy sources for turbulent dissipation in the Andaman Sea (AS) Enhanced tidal dissipation and mixing are found in the deep basin of the AS and are much stronger than those in the Bay of Bengal